Traditions and Beliefs: The Form and Meaning of Ruwatan Desa Among The Muslim Community In Sukapura, Probolinggo Regency - Ulum Fasih; Alif Rohmah Nur Habibah (Batuthah: Jurnal Sejarah Padaban Islam, 2025)
This study explores the Ruwatan Desa tradition in Sukapura, Probolinggo Regency, as a manifestation of the dialectic between Javanese local wisdom and Islamic values. Unlike typical calendrical rituals, the Ruwatan Desa in this region emerged as a situational response to collective trauma following a local tragedy. Using a qualitative-descriptive approach, this research analyzes how ritual symbolism and the process of cultural hybridization function within the community. The results indicate that this tradition serves as a dynamic form of social resilience. Ritual elements, such as the use of all-black attire, are reinterpreted as symbols of spiritual concern (prihatin), while the integration of Tahlil prayers acts as the primary spiritual authority that purifies the ritual’s intent toward Tawhid (oneness of God). Through a process of theological reinterpretation, the Sukapura community has successfully transformed practices once considered animistic into a medium for cultural proselytization (dakwah), where offerings (sesaji) are positioned as the visualization of prayers and alms. Functionally, Ruwatan Desa acts as an effective social healing instrument, providing a space for catharsis to release anxiety and negative stigma following criminal incidents. The mechanism of community during communal dining and prayer, effectively mends social fractures and restores village harmony. This study confirms that Ruwatan Desa is a sophisticated strategy for maintaining the balance between humans, nature, and the Creator.